2022
DOI: 10.1111/zph.12920
|View full text |Cite
|
Sign up to set email alerts
|

Assessing antimicrobial resistance occurrence in the Portuguese food system: Poultry, pigs and derived food, 2014–2018

Abstract: Antimicrobial resistance (AMR) spread in the food system is a major threat to public and animal health. We describe AMR trends in zoonotic bacteria and identify risk factors associated with AMR occurrence in animals and derived food in Portugal.Data from the Portuguese AMR surveillance programme on food-producing animals, 2014-2018, were used. AMR frequencies were calculated for Escherichia coli, Campylobacter and Salmonella in broilers, turkeys, pig populations and their derived food products. AMR-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…However, bacteria with resistance to multiple drugs have increasingly been found because of the overuse and misuse of antibiotics on farms to reduce and prevent the risk of infection [ 2 ]. Pigs and chickens are food-producing animals but are also major reservoirs of organisms with antimicrobial resistance [ 3 , 4 ]. In addition to antibiotic residues in food, antibiotic resistance genes can disseminate between animals and humans via the food chain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, bacteria with resistance to multiple drugs have increasingly been found because of the overuse and misuse of antibiotics on farms to reduce and prevent the risk of infection [ 2 ]. Pigs and chickens are food-producing animals but are also major reservoirs of organisms with antimicrobial resistance [ 3 , 4 ]. In addition to antibiotic residues in food, antibiotic resistance genes can disseminate between animals and humans via the food chain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1). The study revealed a high number of different organisms contamination in poultry products than previously observed in poultry products [18][19][20]. There is a high possibility that harmful organisms will spread from poultry flocks, which have been shown to be common reservoirs, to humans through the food chain [21].…”
Section: Prevalence Of Bacteria In the Poultry Productsmentioning
confidence: 86%
“…Several European states also operate their own monitoring programmes, for example, the Danish Integrated Antimicrobial Resistance Monitoring and Research Programme (DANMAP) in Denmark [54] and the Monitoring of Antimicrobial Resistance and Antibiotic Usage in Animals in the Netherlands (MARAN) programme in the Netherlands [55]. As these monitoring programmes mature, more detailed analyses, e.g., of multiyear trends, will become available, as is the case for Portugal, Denmark, and the USA [56][57][58]. Schrijver et al (2018) reviewed the monitoring programmes in operation in Europe up until 2016 and found marked heterogeneity in sampling and laboratory methodology, as well as in the availability of results (i.e., language and frequency of publication) [59].…”
Section: Antimicrobial Resistance In Escherichia Coli Of Porcine Orig...mentioning
confidence: 99%